Statistical analysis of the factors affecting the selfie addiction among millennials using multiple regression analysis / Nurul Nasya Rahim ... [et al.] - Rahim, Nurul Nasya; Kamarazman, Khairul Najwaa; Shaharudin, Siti Aina Shahidah; Ibrahim, Nurul Bariyah; Ibrahim, Nur Safwati; Mohd Fauzi, Noor Zafarina; Hamzah, Nor Hazreeni; Mohamed Zukri, Shamsunarnie (Unit Penerbitan UiTM Kelantan, 2021)
Selfie has been a part of people's daily routine and it became a world phenomenon since people nowadays easily taking selfie using smartphone, digital camera or webcam almost every second. The photos taken uploaded with a unique caption and tons of hash tags in social networking platform especially among young generations. The aim of the study was to identify the relationship between independent variables (narcissism, loneliness, self-esteem) and the selfie addiction. Besides, to determine the factors (gender, narcissism, loneliness, self - esteem) that are influencing the addiction towards selfie among millennials. Cross sectional survey design was used and the target population for this study involved all students in Universiti Teknologi Mara (UiTM) Kelantan, Kampus Kota Bharu. Proportionate Stratified sampling technique was used to collect the data. A set of questionnaires was used as a measuring instrument for data collection and there were 276 respondents of undergraduated students were selected to complete the questionnaires. Correlation analysis results indicate that there are significant positive relationships between the independent variables (narcissism, loneliness, self-esteem) and the selfie addiction. Multiple regression analysis also revealed that the selfie addiction among youngsters was influenced by gender, narcissism, and self - esteem variables.